AGENCY PROBLEM DALAM PERSPEKTIF MANAJEMEN BARAT DAN ISLAM - Satiri (Jurnal Satya Mandiri Manajemen dan Bisnis, 2017)
Every interest that involve two individuals or two parties could cause something that is called agency problem, where both parties do not have the same information and interest ( asymetric information). Agency problem could happens in conventional (western) management or Islamic management. It involve two types of asymetric information, those are adverse selection and moral hazard. Since the very beginning agency problem was a big problem in Islamic finance management. This is because Islamic finance management has a trust value greater than in western. That is why track record become one of the most important indicator for minimizing agency problem.